The Effect of Managerial Ownership, Company Size, and Profitability on Firm Value With Profit Management as Moderation Variables - Sri Ayem; Yasinta Angelina Seldis (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Increasing the value of the company is carried out to obtain profits (profit). This research proves that managerial ownership of firm size and profitability to firm value: Profit management as a moderating variable. The purpose of this study is to determine managerial ownership, company size, profitability to company value and also to determine the effect of profit management as a moderate variable in moderating managerial ownership, company size and profitability to company value. Manufacturing companies in the Food and Beverag subsector listed on the Indonesia Stock Exchange (IDX) in 2018-2020 are the samples used in this study. Sampling using purposive sampling method and obtained 13 companies with data processing 31 annual financial statements and annual reports. This research method uses multiple linear analysis and moderate regression analysis. Data analysis using descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing and absolute analysis value tests using SPSS version 20.The results prove that managerial ownership has no effect on company value, company size variables have a positive effect on company value, profitability variables have no effect on company value. Profit management variables weaken the influence of managerial ownership on company value, profit management can strengthen the positive influence of company size on company value, profit management can weaken the effect of profitability on company value.